2016
DOI: 10.1186/s12953-016-0100-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteome analysis of abdominal adipose tissues between fat and lean broilers

Abstract: BackgroundThe molecular mechanism underlying broiler fat deposition is still poorly understood.MethodCurrently, we used two-dimensional gel electrophoresis (2DE) to identify differentially expressed proteins in abdominal adipose tissues of birds at 4 week of age derived from Northeast Agricultural University broiler lines divergently selected for abdominal fat content (NEAUHLF).ResultsThirteen differentially expressed protein spots were screened out and identified by matrix-assisted laser desorption-ionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Phosphorylated HSP27 promotes autophagy and hepatic lipid clearance via autophagy-lysosome pathway in human hepatic cells [ 34 ]. We previously found that HSP27 protein was down-regulated in the abdominal adipose tissue of fat birds [ 12 , 13 ], and here we found that HSP27 was down-regulated in the liver tissue of fat birds at E7 and E12. Taken together, our data strongly suggest that HSP27 might be important for hepatic lipid metabolism in chickens.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Phosphorylated HSP27 promotes autophagy and hepatic lipid clearance via autophagy-lysosome pathway in human hepatic cells [ 34 ]. We previously found that HSP27 protein was down-regulated in the abdominal adipose tissue of fat birds [ 12 , 13 ], and here we found that HSP27 was down-regulated in the liver tissue of fat birds at E7 and E12. Taken together, our data strongly suggest that HSP27 might be important for hepatic lipid metabolism in chickens.…”
Section: Discussionsupporting
confidence: 72%
“…However, no transcriptional difference for ApoA-I in the embryonic liver was found between the fat and lean broilers at E17, suggesting the ApoA-I may be regulated at the translational level. We previously examined ApoA-I and its association with fat deposition using genetics, gene expression and proteomics methods in adipose tissues [ 12 , 13 ]. ApoA-I is a major component of high-density lipoprotein (HDL) in the plasma [ 26 ], and can promote cholesterol efflux from peripheral tissues to the liver to keep body cholesterol in balance [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since 1996, we established two broilers lines based on divergent selection on abdominal fat percentage and plasma very low-density lipoprotein (VLDL) concentration (NEAUHLF) [3], which is an ideal model for studying the molecular basis of adipose tissue growth and development. As a result, we have discovered a number of key genes underlying fat deposition through microarray [4][5] and two-dimensional gel electrophoresis technologies, such as adipocyte fatty acid binding protein (A-FABP) and Apolipoprotein A-I (Apo-AI) [6][7]. However, the molecular mechanism for abdominal fat deposition differences between fat and lean broiler lines remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition of fat in the body has a precise temporal and spatial sequence (Gri n et al 1987). The measurement results show that the sequence of fat deposition sites in broilers is abdominal organs, subcutaneous tissues, muscle bundles, and nally, muscle bers (Wang et al 2009;Wu et al 2016). The high-intensity breeding selection causes the growth speed of the broiler rapidly, almost reaching its physiological limit, leading to a major reduction in the quality of the meat.…”
Section: Discussionmentioning
confidence: 93%